Comprehensive Alzheimer's pathology is induced by P. gingivalis infection: COR388 and other gingipain inhibitors protect against synaptic loss: Molecular and cell biology/synaptic disruption. (7th December 2020) - Ermini, Florian; Haditsch, Ursula; Roth, Theresa; Rodriguez, Leo; Broce, Sean; Raha, Debasish; Nguyen, Mai; Hancock, Sandy; Cecere, Thomas; Detke, Mike; Kapur, Shirin; Holsinger, Leslie J.; et al.
Abstract: Background: Porphyromonas gingivalis and its proteolytic virulence factors lysine‐gingipain (Kgp) and arginine‐gingipain (Rgp) are emerging as major etiologic agents in the pathogenesis of Alzheimer's disease (AD). We have previously reported that gingipains colocalize with neuronal cell bodies in over 90% of AD brains studied and the presence of gingipains strongly correlates with tau pathology. We have found tau protein to be a substrate for both Kgp and Rgp and have identified over forty cleavage sites combined. Here we used iPSC‐derived neuron cultures and neuron‐astrocyte‐microglia co‐cultures to investigate the neuropathological mechanisms resulting from persistent infection with P. gingivalis and gingipain exposure and highlight the therapeutic potential of gingipain inhibitors. Method: IPSC derived neuron cultures and neuron‐astrocyte‐microglia co‐cultures were infected with P. gingivalis and analyzed by high content screening (HCS), confocal microscopy, transmission electron microscopy (TEM), protein and RNA expression analysis. Result: Intracellular P. gingivalis bacteria were observed in neurons for 3 days or longer after infection. Infection produced significant synaptic loss that was completely prevented by Kgp and Rgp inhibitors including COR388. Using electron microscopy, we found an accumulation of autophagic vacuoles in dystrophic neurites reminiscent of ultrastructural findings in AD brains. Furthermore, gingipain exposure resulted in acute fragmentation of tau and increased tau phosphorylation, resulting in destabilized microtubules and disrupted vesicle transport. Transport disruption by gingipains accounted for the accumulation of autophagic vacuoles in dystrophic neurites, as no dystrophic neurites were observed in cultures treated with gingipain inhibitors. When co‐cultures of microglia, astrocytes and neurons were infected, activated microglia displayed the highest number of internalized bacteria and responded to infection by upregulation of inflammatory markers associated with AD pathology. Conclusion: We demonstrate in an in vitro model system that P. gingivalis infection can result in a neurodegenerative phenotype consistent with pathology found in Alzheimer's disease. With this model we show that exposure of neurons to P. gingivalis infection results in synaptic loss and dystrophic neurites which can be prevented by gingipain inhibitors.